Studi Kasus: Implementasi Board Game Arena Jelajah Bencana Berbasis Augmented Reality Sebagai Media Pembelajaran IPS Pada Kelas V SDN Surgi Mufti 4: - Sri Kurnia Damayanti; Raudah, Raudah; Noor Afiyanti, Irma; Ferdiyansyah, Aldy; Asniwati, Asniwati (Journal of Teaching and Elementary Education, 2025)
This study examines the implementation of the Board Game learning media "Arena Jelajah Bencana" based on Augmented Reality as a solution to the problems of social studies learning in class V SDN Surgi Mufti 4. Using a qualitative descriptive approach through a case study, the study was conducted on 35 students and homeroom teachers of class V as informants. Data collection was carried out through interviews, observations, and documentation, with data analysis using triangulation techniques. The results of the study showed that previously social studies learning at the school used a projector to display videos from YouTube and the Merdeka Mengajar Platform (PMM), which caused students to tend to be passive. The Board Game media "Arena Jelajah Bencana" integrated with Augmented Reality technology succeeded in creating interactive and contextual learning through 3D visual simulations of disaster events, group collaboration, and educational challenges. The results of the study revealed the positive impact of the implementation of the media in four main aspects: (1) students' learning motivation is reflected through curiosity and meaningful questions that arise during learning; (2) the transformation of students' active participation, especially those who were previously passive, to be more courageous in group discussions; (3) development of interest in learning about natural disaster material, shown by high enthusiasm and longer attention duration; and (4) students' ability to explain the concept of natural disasters in a structured manner shows good learning outcomes,